Eosinophilic Ureteritis Causing Ureterohydronephrosis: A Case Report - Bajracharya, Uspal Bahadur; Sah, Anil Kumar; Baral, Hari; Sigdel, Ghanasham; Shrestha, Guna Kumar; Adhikari, Rojan (Medical Journal of Shree Birendra Hospital, 2021)
Eosinophilic ureteritis is a rare cause of ureteric stricture causing hydroureteronephrosis. The exact aetiology of this condition is still unknown. This condition has been described in relation to atopy, hypereosinophilic syndrome and prior ureteral interventions. The histopathology is the conclusive diagnostic modality. The surgical resection of the ureteric stricture part with end-to-end anastomosis is usually successful. Herein, we report a case of a 19-year-old woman, who presented with right flank pain. With imaging and diagnostic ureteroscopy, the case was diagnosed as eosinophilic ureteritis. The case was successfully managed with resection of the stenosing part and end-to-end anastomosis. No cases of the disease have been reported until now in Nepal.